Experimental investigation of fast electron transport through Kα imaging and spectroscopy in relativistic laser-solid interactions - Köster, P; Akli, K; Batani, D; Baton, S; Evans, R; Giulietti, A; Giulietti, D; Gizzi, L; Green, J; Koenig, M; Labate, L; Morace, A; et al. (2009)
We report on experimental fast electron transport studies performed in the relativistic laser intensity interaction regime. The investigation has been carried out in the long-pulse (0.6 ps) regime relevant for the fast ignitor scheme in the inertial confinement fusion concept. Multilayer targets containing different materials were irradiated. Here we show the results concerning SiO2 or Al layers, respectively. The Kα radiation from a Cu tracer layer on the target rear side was found to be enhanced by a factor of about 8 with the irradiation of SiO2 targets with respect to the Al targets. The possible origin of this observation is discussed. © 2009 IOP Publishing Ltd.